DOI: 10.25148/etd.fi13040403
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Habitat on the Reproductive Ecology of the Amazonian Palm, Mauritia flexuosa, in Roraima, Brazil

Abstract: ACKNOWLEDGMENTSThroughout this dissertation, many people have graciously shared their shared their time, expertise, creativity, and support with me; to them, I am grateful. Suzanne Koptur, my major professor, consistently supported my outlandish idea of studying a species that most people in the US have never heard of, and in a region where few US or European scientists venture. Despite the many difficulties I encountered along the way, Suzanne continued to encourage me while giving me the intellectual and emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 73 publications
(107 reference statements)
0
4
0
2
Order By: Relevance
“…Results showed that fruit production was associated with precipitation, increased cloudiness, and minimum air temperatures. Haugaasen and Peres (2005) reported that lengthy green fruit production was more common in flooded Amazon forests and particularly in M. flexuosa (Da Silva 2009;Tobler 2010;Khorsand-Rosa 2013). However, ripe fruits exhibited a peak between June and July in both years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Results showed that fruit production was associated with precipitation, increased cloudiness, and minimum air temperatures. Haugaasen and Peres (2005) reported that lengthy green fruit production was more common in flooded Amazon forests and particularly in M. flexuosa (Da Silva 2009;Tobler 2010;Khorsand-Rosa 2013). However, ripe fruits exhibited a peak between June and July in both years.…”
Section: Discussionmentioning
confidence: 99%
“…Here, these conditions affected not only the number of females shedding fruit (24 females ha -1 in 2010-2011 compared to 35 females ha -1 in 2012), but also fruit production, which was much lower in the first (0.9 ton ha -1 year -1 ) compared with the second (2.2 ton ha -1 year -1 ) year. Haugaasen and Peres (2005) showed interannual fruiting variation in species from Amazon flooded forests and in many other tropical forest species due to strong changes in rainfall and temperature, with ENSO responsible for the most notable variability in the Amazon (Phillips et al 2010;Khorsand-Rosa 2013). However, new data now indicate other climate forces, such as the Atlantic SST (Espinoza et al 2011;Marengo et al 2013), might also influence Amazon plant phenology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En Jenaro Herrera (río Ucayali) el 10% de la floración ocurre de febrero a marzo y el 90% desde agosto hasta diciembre con un pico en setiembre con 62%. De acuerdo con Khorsand (2013), el ciclo fenológico de la M. flexuosa es anual, sin embargo, Hernández et al (2004) señalan que su ciclo fenológico es supra anual, indicando que el período reproductivo no está sujeto exclusivamente por condiciones estacionales. En ese contexto, teniendo en cuenta que la fenología de las especies es alterada de acuerdo a su localización geográfica y con los elementos del clima, el objetivo en este trabajo fue determinar la influencia de la precipitación pluvial y la temperatura del aire sobre la fenología de M. flexuosa en los distritos de Campo Verde y Nueva Requena de Ucayali.…”
Section: Introductionunclassified